Pengembangan Permainan Dam Quiz sebagai Sarana Keterbukaan Diri Untuk Siswa SMP Islam Al Huda Lamongan - Pewi Pike Mapala; Sri Panca Setyawati; Khususiyah Khususiyah; Laelatul Arofah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This research is motivated by the phenomenon of student openness, so reluctant to express themselves. This condition resulted in the teacher of Bimbinangan and counseling trying to help students to overcome them by giving advice or guidance conventionally/taditionally. However, this effort is effective, one of which is not using innovative and interesting media. The effort to do the research objective is to develop BK Dam Quiz service media. The development method used is the addie model with three stages: analysis, design, and development. The results of the data analysis show that the DAM-Quiz game is suitable for use by guidance and counseling teachers as a service medium for students who experience low disclosure problems.